2021
DOI: 10.1021/acsami.1c17953
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Weaved Turbostratic Nanodomains Enable Stable Na+ Ion Storage and Micropore Filling is Revealed to be More Unsafe than Adsorption and Deintercalation

Abstract: Advanced wave-shape non-graphitizable carbon sheets are derived, comprising mesoporous weaved turbostratic micropore enabled stable Na + ion storage. The non-graphitizable amorphous characteristics are determined from the obtained two broad diffraction peaks at 22.7°and 43.8°. The observed D-band at 1325 cm −1 and G-band at 1586 cm −1 confirm the disordered graphitic structure, attributed to the measured specific surface area of 54 m 2 g −1 . Mesoporous weaved wave-shape carbon sheet architecture is confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…1s†) confirms the reduced micropore-filling characteristics of plastic waste derived Co/C composite materials, in contrast to the hard carbon anode. 60 The measured BET-specific surface area of the plastic waste derived composite materials was 39 m 2 g −1 for Co-GNP-ZipC (green), 19 m 2 g −1 for Co-GNP-FmC (cyan) and 47 m 2 g −1 for pristine Co-GNP, which are almost six times less than the GNP surface area, 292 m 2 g −1 (Fig. S1b†), and close to graphitic carbon and Co metal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1s†) confirms the reduced micropore-filling characteristics of plastic waste derived Co/C composite materials, in contrast to the hard carbon anode. 60 The measured BET-specific surface area of the plastic waste derived composite materials was 39 m 2 g −1 for Co-GNP-ZipC (green), 19 m 2 g −1 for Co-GNP-FmC (cyan) and 47 m 2 g −1 for pristine Co-GNP, which are almost six times less than the GNP surface area, 292 m 2 g −1 (Fig. S1b†), and close to graphitic carbon and Co metal.…”
Section: Resultsmentioning
confidence: 99%
“…58,59 However, the decreased angle of the slope and the elevated at plateaus conrm the mesoporous characteristics compared to the micropores, and the observed plateaus closely match with the graphitic N 2 adsorption-desorption isotherm curve. 42,43,60 Furthermore, the absence of strong N 2 adsorption at less than 0.1 relative pressure (Fig. 1s †) conrms the reduced micropore-lling characteristics of plastic waste derived Co/C composite materials, in contrast to the hard carbon anode.…”
Section: Structural Characterization Of Plastic Waste Derived Graphit...mentioning
confidence: 94%
“…Accordingly, MMC studies of the layered P2-type NaCoO 2 cathode at the discharge state revealed higher released total heat energies (740 J g –1 ) and decreased onset temperature (141 °C) than charge conditions (550 J g –1 and 191 °C) for an exothermic reaction at the thermal runaway event and showed a discharge state at 2 V unsafe than charge conditions . Furthermore, the MMC studies of the micropore-filling Na + ion mechanism for a mesoporous hard carbon anode showed a higher released total heat energy of 721 J g –1 than adsorption (471 J g –1 ), which revealed micropore-filling Na + ion storage to be unsafe than adsorption . Hence, the in situ MMC technique can be used to study the thermal stability of the PI separator and calculate exothermic released heat energies at the thermal runaway event of LIBs to use in high-power applications and renewable energy technologies such as solar, wind, and so on.…”
Section: Introductionmentioning
confidence: 98%
“…31 Furthermore, the MMC studies of the micropore-filling Na + ion mechanism for a mesoporous hard carbon anode showed a higher released total heat energy of 721 J g −1 than adsorption (471 J g −1 ), which revealed micropore-filling Na + ion storage to be unsafe than adsorption. 32 Hence, the in situ MMC technique can be used to study the thermal stability of the PI separator and calculate exothermic released heat energies at the thermal runaway event of LIBs to use in high-power applications and renewable energy technologies such as solar, wind, and so on. In this study, the PI-Al 2 O 3 membrane was synthesized by an electrospinning technique and the chemical constituents of carbonyl and imide functional groups were characterized.…”
Section: Introductionmentioning
confidence: 99%